2010
DOI: 10.1590/s1676-06032010000100020
|View full text |Cite
|
Sign up to set email alerts
|

Fitossociologia de um Cerrado denso em área de influência de torre de fluxo de carbono, Pé-de-Gigante, Parque Estadual de Vassununga, SP

Abstract: O domínio do Cerrado compreende uma área contínua nos estados centrais do Brasil e áreas disjuntas em outros estados, incluindo São Paulo. Essa vegetação ocupava originalmente 21% do território brasileiro, restando atualmente apenas 21,6% de sua extensão original. A área recoberta por essa vegetação em São Paulo cobria 14% de sua área total e seus remanescentes recobrem menos de 1% da ocorrência original dessa vegetação. Estudos recentes indicam que o valor da produtividade líquida no Cerrado Pé-de-Gigante (SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
4
1
1
Order By: Relevance
“…ind -1 ) in our study were greater than those reported by Felfili et al (2004). Moreover, the absolute density, the basal area and Shannon's diversity index observed in our study were greater than those obtained in other ''Dense Cerrado'' areas (Andrade et al 2002;Latansio-Aidar et al 2010;Pinheiro and Durigan 2012).…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…ind -1 ) in our study were greater than those reported by Felfili et al (2004). Moreover, the absolute density, the basal area and Shannon's diversity index observed in our study were greater than those obtained in other ''Dense Cerrado'' areas (Andrade et al 2002;Latansio-Aidar et al 2010;Pinheiro and Durigan 2012).…”
Section: Discussioncontrasting
confidence: 85%
“…Of the species with the greatest importance values recorded in our study, A. multiflorum, B. tomentosa, E. nitens, M. crassiramea, P. emarginatus, Q. grandiflora, Q. parviflora, T. vulgaris and X. aromatica deserve special attention, as they, combined, were responsible for approximately 37% of the importance value. Special notice should be given to Q. parviflora, Q. grandiflora and X. aromatica, as they have wide geographical distributions and are therefore listed among the species with the highest importance values in other ''Cerrado'' areas (Andrade et al 2002;Latansio-Aidar et al 2010;Bueno et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study area is located in the city of Santa Rita do Passa Quatro, São Paulo state, Brazil, in the Pé de Gigante Forest Reserve (PEG), with an area of 1060 hectares, covered with woodland savanna vegetation (Figure 1, with dense Cerrado predominantly of Cerradão and Cerrado sensu stricto physiognomies [20,21] and other small areas of campo and deciduous forest, with a surrounding eucalyptus plantation to the west and north, and crops to the east and south.…”
Section: Study Area and Micrometeorological Measurementsmentioning
confidence: 99%
“…Em relação à saúde pública, o principal problema está no crescimento das populações humanas em cidades litorâneas, sem acompanhamento na melhoria da infraestrutura de saneamento básico (OLIVEIRA et al, 2010).…”
Section: Identification Of Pathogenic Fungi In Sand Of Calhau Beach unclassified